The Holarctic genus Aeolothrips (Thysanoptera: Aeolothripidae) from Iran, with description of two new species - Alavi, Jalil; Awal, Mehdi Modarres; Fekrat, Lida; Minaei, Kambiz; Manzari, Shahab (Zootaxa, 2015)
Two new species of the genus Aeolothrips are described from northeast of Iran. A. bhattii sp.n. from flowering Caroxylon dendroides is remarkable for its strikingly bicolored body with brown head and last three abdominal segments. A. laurencei sp.n. from flowers of Elaeagnus angustifolia is characterized by its large and dark brown body, all yellow tarsi and fore wings with two brown transverse bands connected posteriorly.